A case series of outcomes in isolated subsegmental pulmonary embolism on ventilation–perfusion imaging. Issue 7 (July 2018) - Mallorie, Amy; Chan, Kenneth; Ioannidis, Stefanos; Stubbs, Matthew; Navalkissoor, Shaunak; Wagner, Thomas
Abstract : Objectives: The risk of recurrent venous thromboembolic disease and the management of patients with isolated subsegmental pulmonary embolism (SSPE) remain unclear. We sought to assess the long-term clinical outcome of patients with isolated SSPE demonstrated by isolated subsegmental mismatch found on ventilation/perfusion (V/Q) scans. Patients and methods: We performed a retrospective observational study of 1300 consecutive patients with suspected pulmonary embolism who underwent index V/Q single-photon emission computed tomography between 2012 and 2013. Forty (3%) patients were found to have isolated SSPE identified on V/Q scan. Of the 40 patients with isolated SSPE on V/Q scan, 19 underwent further investigation with computed tomography pulmonary angiogram (CTPA) within 48 h. Results: Among 19 patients who had corroborating CTPA performed concurrently, 94.7% of the SSPEs identified on V/Q were not detectable on CTPA. Of the 40 patients, 10 (25%) were anticoagulated. In a median follow-up of 3.28±0.55 years, all-cause mortality occurred in two patients, recurrence of suspected venous thromboembolism (VTE) occurred in 12 (30%) of 40 patients, but none had confirmed recurrent thromboembolism on further imaging. In the 40 patients with SSPE on V/Q, there was no difference in the risk of recurrence of suspected VTE or mortality between patients treated with anticoagulation and not treated (hazard ratio: 2.04, 95% confidence interval: 0.75–7.28). Conclusion: In this case series, a large proportion of patients with isolated SSPE on V/Q imaging were not identified on corroborating CTPA performed within 48 h. In patients with isolated SSPE (identified by isolated subsegmental mismatch on V/Q single-photon emission computed tomography), we found no difference in risk of recurrent suspected VTE or all-cause mortality in those treated with anticoagulation and those not treated.